The Rocky‐Like Behavior of Cometary Landslides on 67P/Churyumov‐Gerasimenko. Issue 24 (27th December 2019) - Lucchetti, Alice; Penasa, Luca; Pajola, Maurizio; Massironi, Matteo; Brunetti, Maria Teresa; Cremonese, Gabriele; Oklay, Nilda; Vincent, Jean‐Baptiste; Mottola, Stefano; Fornasier, Sonia; Sierks, Holger; Naletto, Giampiero; et al.
Abstract: Landslides have been identified on several solar system bodies, and different mechanisms have been proposed to explain their runout length. We analyze images from the Rosetta mission and report the global characterization of such features on comet 67P/Churyumov‐Gerasimenko's surface. By assuming the height to runout length as an approximation for the friction coefficient of landslide material, we find that on comet 67P, this ratio falls between 0.50 and 0.97. Such unexpected high values reveal a rocky‐type mechanical behavior that is much more akin to Earth dry landslides than to icy satellites' mass movements. This behavior indicates that 67P and likely comets in general are characterized by consolidated materials possibly rejecting the idea that they are fluffy aggregates. The variability of the runout length among 67P landslides can be attributed to the different volatile content located in the top few meters of the cometary crust, which can drive the mass movement. Plain Language Summary: Comet 67P Churyumov‐Gerasimenko has been imaged with unprecedented spatial detail thanks to the high‐resolution OSIRIS camera (Optical, Spectroscopic and Infrared Remote Imaging System) on board the Rosetta spacecraft. 67P is characterized by an extremely diverse morphology comprising different surface features such as rough consolidated terrains, smooth plains, unconsolidated mantles, pits, fractures, cliffs, cuestas, ubiquitous boulders, and layers. The peculiarity of 67P is also reflected by the widespread presence of landslides. By using high‐resolution images, we analyze the shape and aspect ratio of the landslides located on comet 67P finding a mechanical behavior of the cometary material that is more akin to Earth dry landslides than to icy satellites' mass movements. These results make 67P a very peculiar object, mainly composed by ices and refractory materials but characterized by rocky‐type properties rather than icy‐type characteristics. In addition, the considerable variability among the different landslides of 67P suggests that different volatile contents located in the top few meters of the cometary crust play a fundamental role on mass movement, hence being a general indicator for the subsurface cometary heterogeneities. Key Points: The height to runout length (H/L) of comet 67P/Churyumov‐Gerasimenko landslides ranges between 0.50 and 0.97 67P landslide reveal a rocky‐type mechanical behavior indicating that comets are made by consolidated materials The H/L variability is an indicator of the different volatile content located in the top few meters of the cometary crust